2020
DOI: 10.1021/jacs.0c06858
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Oxidation Reactions at the Air–Water Interface

Abstract: Chemistry on water is a fascinating area of research. The surface of water and the interfaces between water and air or hydrophobic media represent asymmetric environments with unique properties that lead to unexpected solvation effects on chemical and photochemical processes. Indeed, the features of interfacial reactions differ, often drastically, from those of bulk-phase reactions. In this Perspective, we focus on photoinduced oxidation reactions, which have attracted enormous interest in recent years because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 213 publications
(443 reference statements)
1
55
0
Order By: Relevance
“…The significance of heterogeneous photochemistry has been highlighted by different authors, in particular in relation to the study of organic matter oxidation in the atmosphere (23)(24)(25)(26)(27)(28). Many processes appear to be accelerated compared to the same processes in the gas phase or in bulk solution.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The significance of heterogeneous photochemistry has been highlighted by different authors, in particular in relation to the study of organic matter oxidation in the atmosphere (23)(24)(25)(26)(27)(28). Many processes appear to be accelerated compared to the same processes in the gas phase or in bulk solution.…”
Section: Significancementioning
confidence: 99%
“…Many processes appear to be accelerated compared to the same processes in the gas phase or in bulk solution. Absorption energy shifts, band broadening, surface accumulation, or the diminution of solvent-cage effects operating in bulk solution are plausible causes for the photochemical rate increase, although the mechanisms of surface-enhanced photochemistry remain to be fully understood (23,26,29).…”
Section: Significancementioning
confidence: 99%
“…Photosensitization appears to be particularly meaningful at surfaces and interfaces. [5][6][7][8][9] The study of photochemical processes at aqueous interfaces has deserved numerous recent theoretical and experimental studies because the solvation effects at the interface appear to enhance the reactivity, compared to gas phase or bulk water solution (for recent reviews and perspectives, see for instance Ref 8,[10][11][12][13] ). This heterogeneous chemistry has great atmospheric and environmental significance, 3,[14][15][16] but presents also strong implications for the development of efficient technologies in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions can also be promoted at the surface of atmospheric aerosol particles (14)(15)(16). It has been reported that interface effects and surface charging can cause acceleration of chemical reactions in microdroplets and nanodroplets (14,(17)(18)(19)(20), observations that have especially sparked interest in the use of microdroplets as new powerful reactors for chemical synthesis (15,16).…”
mentioning
confidence: 99%